Global and diffuse solar irradiances in urban and rural areas in southeast Brazil - Codato, G.; Oliveira, A. P.; Soares, J.; Escobedo, João Francisco [UNESP]; Gomes, E. N. [UNESP]; Pai, A. D. [UNESP] (Springer Wien, 2008)
The seasonal evolution of daily and hourly values of global and diffuse solar radiation at the surface are compared for the cities of São Paulo and Botucatu, both located in Southeast Brazil and representative of urban and rural areas, respectively. The comparisons are based on measurements of global and diffuse solar irradiance carried out at the surface during a six year simultaneous period in these two cities. Despite the similar latitude and altitude, the seasonal evolution of daily values indicate that São Paulo receives, during clear sky days, 7.8% less global irradiance in August and 5.1% less in June than Botucatu. on the other hand, São Paulo receives, during clear sky days, 3.6% more diffuse irradiance in August and 15.6% more in June than Botucatu. The seasonal variation of the diurnal cycle confirms these differences and indicates that they are more pronounced during the afternoon. The regional differences are related to the distance from the Atlantic Ocean, systematic penetration of the sea breeze and daytime evolution of the particulate matter in São Paulo. An important mechanism controlling the spatial distribution of solar radiation, on a regional scale, is the sea breeze penetration in São Paulo, bringing moisture and maritime aerosol that in turn further increases the solar radiation scattering due to pollution and further reduces the intensity of the direct component of solar radiation at the surface. Surprisingly, under clear sky conditions the atmospheric attenuation of solar radiation in Botucatu during winter - the biomass burning period due to the sugar cane harvest - is equivalent to that at São Paulo City, indicating that the contamination during sugar cane harvest in Southeast Brazil has a large impact in the solar radiation field at the surface.